Annals of the American pulpit: or, Commemorative notices of distinguished American clergymen of various denominations : from the early settlement of the country to the close of the year eighteen hundred and fifty-five : with historical introductions - Sprague, William Buell (Robert Carter & Brothers, 1857)
v. 1-2. Trinitarian Congregational. 1857 -- v. 3-4. Presbyterian. 1859 -- v. 5. Episcopalian. 1859 -- v. 6. Baptist. 1860 -- v. 7. Methodist. [1859] -- v. 8. Unitarian Congregational. 1865 -- v. 9. Lutheran. Reformed Dutch. Associate. Associate Reformed. Reformed Presbyterian. 1869.